Dynamic platelet function on von Willebrand factor is different in preterm neonates and full‐term neonates: changes in neonatal platelet function. (20th August 2016) - Cowman, J.; Quinn, N.; Geoghegan, S.; Müllers, S.; Oglesby, I.; Byrne, B.; Somers, M.; Ralph, A.; Voisin, B.; Ricco, A. J.; Molloy, E. J.; Kenny, D.
Abstract : Essentials It is unclear if platelet function differs between preterm and full‐term neonates. Platelet behavior was characterized using a flow‐based assay on von Willebrand Factor (VWF). Preterms had increased platelet interaction with VWF and glycoprotein Ibα expression. Platelets from preterm neonates behave differently on VWF compared to full‐term neonates. Summary: Background: Very low birth weight (VLBW) preterm neonates have an increased risk of hemorrhage‐related morbidity and mortality as compared with their full‐term counterparts. It is unclear whether platelet function differs between preterm and full‐term neonates. This is partly because of the large volumes of blood required to perform standard platelet function tests, and the difficulty in obtaining such samples in neonates. Objectives: This study was designed to characterize platelet behavior in neonates with a physiologic flow‐based assay that quantifies platelet function in microliter volumes of blood under arterial shear. Methods: Blood from VLBW preterm neonates of ≤ 32 weeks' gestation ( n = 15) and full‐term neonates ( n = 13) was perfused under arterial shear over surface‐immobilized von Willebrand factor (VWF). Platelet behavior was recorded by digital‐image microscopy and analyzed. Surface expression of platelet glycoprotein (GP) Ibα and GPIIIa of VLBW preterm and full‐term neonates was also measured. Results: VLBW preterm neonates had increased numbers of platelets interacting with VWF, and increased GPIbα expression on the platelet surface. Despite the increased numbers of VWF interactions as reflected by flow‐driven platelet translocation along the protein surface, no significant differences were observed in the numbers of platelets that adhered in a stationary fashion to VWF. Platelets from VLBW preterm neonates and those from full‐term neonates behaved differently on VWF. Conclusions: These differences in platelet function may contribute to the higher incidence of bleeding observed in VLBW preterm neonatal populations, or may represent a compensatory mechanism to counteract this risk of bleeding.